In silico modelling and structural dynamics of PSY1R kinase domain and its interaction with SERK1 kinase - Ruhee, Noshin Nawer (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.